Periprocedural myocardial infarction following percutaneous coronary intervention at Charlotte Maxeke Johannesburg Academic Hospital - Tsabedze, Nqoba Israel (My University, 2017)
The very first coronary artery balloon angioplasty is reported to have been performed by Gruntzig in 1977.1 Subsequently to this, over the past 40 years, there have been significant advances in coronary angiography and intervention. Coronary artery interventional techniques have evolved and improved significantly. There have been considerable device developments, new generation stents and novel antiplatelet therapy which have all proved to reduce the incidence of the primary periprocedural complications associated with percutaneous coronary intervention (PCI). [No abstract provided. Information taken from introduction]
Original published work submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine (Internal Medicine) 18 October, 2017.
Keywords: Myocardial Infarction; Percutaneous Coronary Intervention; Coronary Disease